Diagnostics of Level of Formation of Motivational, Activity and Behavioral Components of Ecological Culture of Personality of Future Teacher: Application of Method by G. E. Zalessky - I. P. Shutova; N. V. Osintseva (Научный диалог)
This article deals with the problem of diagnostics of level of formation of motivational and behavioral components of ecological culture of the future teacher’s personality. The authors believe that the process of development of these components reflects the dynamics of formation of the investigated personality traits. The essence and the notion of ecological culture of personality is determined. Its basic structural and functional components are revealed. Special attention is paid to the development of the motivational component associated with the development in the students of axiological and conceptual structures (motives, needs, etc.), which in general determine the focus on ecology friendly activities. The analysis of the methods devoted to questions of formation of ecological culture and education of students is made. The study showed that most of them do not address the issue of identifying the nature of the personal dispositions of the subjects. To solve the problem of the study, the possibility of applying the value-normative method developed by professor G. E. Zalessky for the diagnosis of the value-motivational units of personality is proved. The authors present their development and results of testing of the diagnostic methods. It is noted that this development allows to assess the level of development of intrinsiv ecological motivation of students and the corresponding type of behaviour. It is proved that, given the nature of the interaction of three critical components of ecological culture of the individual - cognitive, motivational and behavioral - it is possible to obtain a preliminary typology of level of ecological culture of the subjects.